Pengaruh Air Perasan Wortel Terhadap Warna Ikan Mas Koki (Carrassius auratus) - Naipospos, Jogi; Mulis, Mulis; Suherman, Sutianto Pratama (Fakultas Kelautan dan Teknologi Perikanan - Universitas Negeri Gorontalo, 2024)
Color is one of the reasons ornamental fish are in demand by the community, so farmers need to maintain the color of ornamental fish. This study aims to determine the effect of carrot juice on the color of goldfish. This research was conducted from December to January 2023. The method used was an experimental method with Complete Randomized Design (RAL) with four treatments and three repeats in each test group. Testing is carried out by giving feed with a mixture of carrot juice with different doses. The results showed that the color values in goldfish were different, namely, P0 treatment without giving carrot juice with a color value of 18.54, P1 treatment (10 g/100 ml aquades) with a color value of 18.4, P2 treatment (20 g/100 ml) with a color value of 19.35, P3 treatment (30 g/100 ml) with a color value of 17.67. Analysis of Variance (ANOVA) showed that the effect of carrot juice on the color of goldfish had no significant effect on each treatment with FHitung (0.11) > FTabel (4.07). Water quality parameters during the study were still in normal conditions for the growth of goldfish.